Holocene Antarctic climate variability from ice and marine sediment cores: insights on ocean-atmosphere interaction - Divine, Dmitry; Koç, Nalân; Isaksson, Elisabeth; Nielsen, Simon H; Crosta, Xavier; Godtliebsen, Fred (Quaternary Science Reviews, 2010)
Holocene climate variability in the southeast Atlantic sector of the Southern Ocean and Antarctic is assessed and quantified through integration of available marine sediment core and Antarctic ice core data. We use summer sea surface temperature (SSST) and sea ice presence (SIP) reconstructions from two marine sediment cores recovered north (50 °S) and south (53.2 °S) of the present day Antarctic Polar Front (APF), as well as an atmospheric temperature and sea ice proxy from the EPICA ice core from Dronning Maud Land (EDML). We find reasonably good agreement in the timing of climate evolution in the analyzed series. Almost all records show a gradual glacial-to-Holocene climate transition, interrupted by the Antarctic cold reversal around 13 000 cal yr BP, and early Holocene climatic optimum (HCO) at about 11 000 cal yr BP. During the early HCO, the seasonal ice cover retreats to south of 53 °S; it then readvances in the course of the mid- to late Holocene. The maximum winter sea ice edge position during the recent 10 000 years varied mainly within 51–53 °S, with sporadic growth to north of 50 °S, a position similar to that during the last glacial. The onset of the Neoglacial period after ca 4000 yr BP is associated with a steepening of the SSST gradient between the marine core sites, strengthening of the westerlies and cooling in the inland ice sheet. The agreement in timing between elevated SSST during the early HCO and decreased deuterium excess in EDML and other ice cores from different locations in the East Antarctic suggests that the retreat of sea ice during the early HCO and weakening of the APF was a general feature of the East Antarctic climate during that time.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; holocene; iskjerner; klimaendringer; oseanografi; paleoklimatologi

Firn accumulation records for the past 1000 years on the basis of dielectric profiling of six cores from Dronning Maud Land, Antarctica - Hofstede, Coen M; Roderik, S W van de Wal; Kaspers, Karsten Adrian; van den Broeke, Michiel R; Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Lappegard, Gante; Mulvaney, Robert; Oerter, Hans; Wilhelms, Frank (Journal of Glaciology, 2004)
This paper presents an overview of firn accumulation in Dronning Maud Land (DML), Antarctica, over the past 1000 years. It is based on a chronology established with dated volcanogenic horizons detected by dielectric profiling of six medium-length firn cores. In 1998 the British Antarctic Survey retrieved a medium-length firn core from western DML. During the Nordic EPICA (European Project for Ice Coring in Antarctica) traverse of 2000/01, a 160 m long firn core was drilled in eastern DML. Together with previously published data from four other medium-length ice cores from the area, these cores yield 50 possible volcanogenic horizons. All six firn cores cover a mutual time record until the 29th eruption. This overlapping period represents a period of approximately 1000 years, with mean values ranging between 43 and 71 mm w.e. The cores revealed no significant trend in snow accumulation. Running averages over 50 years, averaged over the six cores, indicate temporal variations of5%. All cores display evidence of a minimum in the mean annual firn accumulation rate around AD 1500 and maxima around AD 1400 and 1800. The mean increase over the early 20th century was the strongest increase, but the absolute accumulation rate was not much higher than around AD 1400. In eastern DML a 13% increase is observed for the second half of the 20th century.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; paleoklimatologi

Snow grain-size measurements in Antarctica - Gay, Michael; Fily, Michel; Genthon, Christophe; Frezzotti, Massimo; Oerter, Hans; Winther, Jan-Gunnar (Journal of Glaciology, 2002)
Grain-size is an important but not well-known characteristic of snow at the surface of Antarctica. In the past, grain-size has been reported using various methods, the reliability, reproducibility and intercomparability of which is not warranted. In this paper, we present and recommend, depending on available logistical support, three techniques of snow-grain sampling and/or imaging in the field as well as an original digital image-processing method, which we have proved provides reproducible and intercomparable measures of a snow grain-size parameter, the mean convex radius. Results from more than 500 samples and 3000 images of snow grains are presented, which yield a still spatially limited yet unprecedentedly wide picture of near-surface snow grain-size distribution from fieldwork in Antarctica. In particular, except at sites affected by a very particular meteorology, surface grains in the interior of the ice sheet are uniformly small (0.1–0.2 mm). The climate-related increase of grain-size with depth through metamorphism is, as expected, not spatially uniform. Our Antarctic snow grain-size database will continue to grow as field investigations bring new samples, images and measures of snow grain.
Keywords: Antarktis; glasiologi; paleoklimatologi

Klimavariasjoner gjennom de siste 45 000 14C år i Weddellhavet, Antarktis - Larsen, Anne Marit Løland (Universitetet i Bergen, 2001)
Publication Title: Institutt for geovitenskap Volume: M.Sc.
Keywords: Sørishavet; Weddellhavet; maringeologi; paleoklimatologi; sedimenter